(untitled) (Eurasian Journal of Religious Studies, 2021)
Although the Turkic people have the same origin, their beliefs do not coincide, therefore it is difficult to study the religious beliefs of the Turkic people. The religious and theological paradigm of Turkology is very extensive. The strategic direction of theological Turkology is the scientific analysis of the historical and political factors of the adoption of a particular religion by the Turkic people of different religions, clarification of the system of common values ​​of the Turks of at least one religious class, grouping them according to genealogical and linguistic similarities. The paper aims to identify traces of the idea of "Tengrism" in the worldview of modern Turks through the content of Turkic proverbs and sayings. The continuity and interaction of the common Turkic mythological and religious worldviews are differentiated on the basis of a single paremiological meaning and semantic range of keywords. It is defined that the attributes of the idea of Tengrism in the language of Turkic written monuments of the VI-IX centuries are also reflected in the content of Proverbs and sayings of modern Turkic peoples who profess Islam (Kazakh, Karakalpak, Kyrgyz, Bashkir, and Tatar). The synonymic meaning and common symbolic meanings of the theonyms "Tengir", "Allah", "God", which form the dominant words in Proverbs and sayings, are analyzed. The influence of the semantic features of the supporting/dominant word on the paremiological meaning is considered. One of Turkic Studies’ topical problems is the study of the continuity of the religion of “Tengrism” and Islam through language units, which form the basis of the religious and mythological faith of the Turkic peoples. Key words: paremiology, old Turkic manuscripts, Turkic languages, theonym, the idea of Тengrism